New species and records of Otiothopinae from the Southern Atlantic Rainforest, with notes on the claw tufts in Fernandezina Birabén (Araneae: Palpimanidae) - Castro, Diogo; Baptista, Renner; Grismado, Cristian; Ramírez, Martín (Zootaxa, 2015)
Two new species of Otiothops MacLeay, 1839 (O. atalaia sp. n. and O. goytacaz sp. n.), a new species of Fernandezina Birabén, 1951 (F. jurubatiba sp. n.) as well as the female of F. tijuca Ramírez & Grismado, 1996 are described from the Atlantic Rainforest of southeastern Brazil, in the state of Rio de Janeiro. Scanning electron microscope images of the tarsi of F. jurubatiba sp. n. and F. dasilvai Platnick, Grismado & Ramírez, 1999 show that this genus has claw tufts on the posterior legs, composed of setae of variable structure.